Mechanical determinants of sprinting performance in elite women`s Rugby Sevens - Schuster, J.; McMaster, T.; Samozino, P.; Lacey, S.; Winkelman, N. (Journal of Australian Strength and Conditioning, 2018)
Mechanical running proficiency, as reliably measured by radar and software tools and described by application of horizontal forces, correlates strongly to accelerative sprinting performance in elite women`s rugby sevens athletes. Recent research has validated horizontal force-velocity-power profiling methods and identified key mechanical variables correlated to sprinting performance, which was demonstrated consistently in an elite female rugby sevens cohort.